Mechanical behavior of dowel connection for timber-concrete composite rural bridges - Silva Marques, André Filipe (2020)
This study focuses on the evaluation of the mechanical behavior of two types of connections for intended use in rural Timber-Concrete Composite traffic bridges. The two connection types used were the “X” type connection - XD and the dowel type connection - PD. Firstly, static shear tests in small-scale specimens were performed in both connection types and higher results were obtained for the XD series, both for stiffness and load carrying capacity. Secondly, the PD connection was chosen, based on practical and economical aspects, for further testing also in small-scale specimens, including cyclic tests. The influence of the number of cycles in the connection stiffness and load carrying capacity was evaluated. It was concluded that the load carrying capacity increased after the application of a pre-defined number of load cycles and that the connection stiffness increased 80,6% and 34,1% after 10000 and 1000 cycles, respectively, for different applied load levels. Also the increase of load level in the cyclic tests affected the performance of the connection, leading to a decrease in stiffness.